Strategy for Development of Seaweed Cultivation Production Using the Long Line System Method - Rasjid, Yusniar; Taskirah, Andi (ARRUS Journal of Mathematics and Applied Science, 2024)
This research aims to determine the development of Eucheumaspinosium seaweed cultivation techniques using the long-line method and the quality of seaweed using the long-line method. The samples in this research are seaweed Eucheuma sp. The data collection technique is quantitative data in quantities derived from the shape and cleanliness of seaweed cultivated using the long line method. The data obtained were analyzed using an experimental design (RAL). From the results of the data analysis, it can be seen that cultivating Eucheuma Spinosium seaweed, using node distances of 2cm, 5cm, 10cm, 15cm, and 20 cm, the best node distance to use using the long line method is 10 cm which shows greater growth. fast compared to other distances, but this 10 cm distance still does not affect the quality of the Eucheuma sp seaweed.